ΔFosB induction correlates inversely with CB(1) receptor desensitization in a brain region- dependent manner following repeated Δ(9)-THC administration - Lazenka, Matthew F. (2013)
Repeated Δ(9)-tetrahydrocannabinol (THC) administration produces desensitization and downregulation of cannabinoid type 1 receptors (CB(1)Rs) in the brain, but the magnitude of these adaptations varies among regions. CB(1)Rs in the striatum and its output regions exhibit the least magnitude and slowest development of desensitization and downregulation. The molecular mechanisms that confer these region-dependent differences are not known. The stable transcription factor, ΔFosB, is induced in the striatum following repeated THC administration and could regulate CB(1)Rs. To directly compare the regional profile of ΔFosB induction and CB(1)R desensitization and downregulation, mice were treated with THC (10 mg/kg) or vehicle for 13.5 days. CP55,940-stimulated [(35)S]GTPγS autoradiography and immunohistochemistry were performed to measure CB(1)R desensitization and downregulation, respectively, and ΔFosB expression was measured by immunoblot. Significant CB(1)R desensitization and downregulation occurred in the prefrontal cortex, lateral amygdala and hippocampus; desensitization was found in the basomedial amygdala and no changes were seen in remaining regions. ΔFosB was induced in the prefrontal cortex, caudate-putamen, nucleus accumbens and lateral amygdala. An inverse regional relationship between ΔFosB expression and CB(1)R desensitization was found, such that regions with the greatest ΔFosB induction did not exhibit CB(1)R desensitization and areas without ΔFosB induction had the greatest desensitization, with remaining regions exhibiting intermediate levels of both. Dual immunohistochemistry in the striatum showed both CB(1)R co-localization with ΔFosB in cells and CB(1)R puncta surrounding ΔFosB-positive cells. THC-induced expression of ΔFosB was absent in the striatum of CB(1)R knockout mice. These data suggest that transcriptional targets of ΔFosB might inhibit CB(1)R desensitization and/or that ΔFosB induction could be limited by CB(1)R desensitization.